2012
DOI: 10.1021/ic301546v
|View full text |Cite
|
Sign up to set email alerts
|

A Tripyrrolylmethane-Based Macrobicyclic Triazacryptand: X-ray Structure, Size-Selective Anion Binding, and Fluoride-Ion-Mediated Proton–Deuterium Exchange Studies

Abstract: A new class of tripyrrolylmethane-based triazacryptand with bridgehead carbons and acyclic molecules were synthesized by the Mannich reaction of tripyrrolylmethane with primary or secondary amine hydrochloride and formaldehyde, respectively. The structure of the triazacryptand was determined by X-ray diffraction (XRD) method. The anion binding properties of both the bicyclic and acyclic receptors were studied by (1)H NMR titration method. The binding studies showed that both receptors exhibit very high affinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 96 publications
0
20
0
Order By: Relevance
“…Of particular interest to us is a burgeoning field of ingeniously designed, supramolecular fluoride receptors (21)(22)(23)(24)(25). The binding energies of these are just as large, and sometimes larger than that of the D4R box.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest to us is a burgeoning field of ingeniously designed, supramolecular fluoride receptors (21)(22)(23)(24)(25). The binding energies of these are just as large, and sometimes larger than that of the D4R box.…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, Guchhait et al 125 reported the tripyrrolylmethane-based triazacryptand 84 containing bridgehead carbon atoms. This cryptand as well as several acyclic molecules were obtained via a Mannich reaction involving a formylated tripyrrolylmethane, a secondary amine hydrochloride, and formaldehyde.…”
Section: Bicyclic Anion Receptorsmentioning
confidence: 99%
“…These AEHBs can act as “bridges” between the complexed anions, further offsetting the unfavorable like-charge repulsive interactions that would be otherwise expected. Receptor-stabilized anion–anion complexes, including dimers, trimers, clusters, and polymers, ,, have recently been reviewed independently by Sessler and Flood . It is noteworthy that, almost all of these reported examples involve homo-anion complexes, i.e., the cobound species consist of identical anions.…”
Section: Introductionmentioning
confidence: 99%